PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PENYALAHGUNAAN IZIN TINGGAL OLEH WARGA NEGARA ASING BERDASARKAN UNDANG-UNDANG NOMOR 6 TAHUN 2011 TENTANG KEIMIGRASIAN DI KANTOR KEIMIGRASIAN KELAS I PEKANBARU - Saragih, Jusuf Fransen; Indra, Mexsasai; , Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
As contained in Article 1 number 21 of Law Number 6 Year 2011 on Immigration, Tingga Permit is a permit granted to foreigners by an immigration official or an official of a foreign office to reside in the territory of Indonesia. It permits the stay by foreigners is a provision which is prohibited by law no mor 6 of 2011 on immigration governed by Article 122 which reads, shall be punished with imprisonment for a period of 5 (five) years and a maximum fine of Rp500. 000.000,00 (five hundred million rupiah): a. Any foreigner who deliberately misuses or performs activities that are inconsistent with the intent and purpose of granting a residence permit granted to him; b. Any person who orders or gives opportunity to a foreigner misuses or undertakes activities that are inconsistent with the intent or purpose of granting the residence permit granted to him or her.The type of research or approach done by the author is juridical sosilogical legal research. This research was conducted at the Office of Immigration Class I Pekanbaru. This location was chosen because the criminal case of immigration permit misuse was done by foreigners in Pekanbaru area. In this study the authors menggunakas data sources that can be grouped as beriku: Primary data, ie data obtained directly in the location of research. Secondary data, that is data obtained indirectly through a library (library research).From the research problems that dihad fire by the Immigration Office Class I Pekanbaru, namely: First, the law enforcement carried out by the criminal act of abuse of immigration to the residence permit by foreigners. Second, obstacles or experienced pengahambat factor k piha weld Immigration All I Pekanbaru in conducting law enforcement abuse of a residence permit is the lack of immigration officials is not comparable to the work area. Third, efforts made piha k Immigration Class I Pekanbaru in overcoming one of them is proposing the addition of an immigration office in each district in order to facilitate monitoring of the presence of strangers.Keywords: Law Enforcement-Crime-Abuse-stay permit